The public conversation about vaccines and vaccination against covid-19 on Twitter: an infodemiological study - Lopes, Arthur da Silva (2023)
The present research is infodemiological and aims to characterize the public conversation about the vaccine and vaccination against COVID-19 in Brazil that took place on Twitter. To map the latent topics in the collected data (13.2 million tweets), topic modeling was used. since the efficacy of public vaccination policies is conditioned by its population adhesion. From the results, 50 topics were identified and discussed over the period of analysis, 11 of which have direct potential to promote vaccine hesitancy, categorized into thematic groups, namely Accountability, Public Policies, Conflicts, Bioethics, Experience Reports, Economic Aspects, Conspiracy Theories; and Safety, Efficacy and Importance of Vaccines. There was a strong politicization translated by the most retweeted profiles and hashtags used, not only partisan, but mostly civic, represented by users participation through the manifestation of social control in health.